Penyuluhan Stunting di Desa Pattiro Sompe - Mutmainnah Mutmainnah; Musni Musni; St. Malka; Irawati Irawati (Jurnal Pengabdian Bidang Kesehatan, 2023)
Stunting is problem of chronic malnutrition caused be a long-term deficiency in nutritional intake, characterized by a child’s height not matching that of children his age. One of the causes of stunting in Pattiro Sompe Village is the mother’s lack of knowledge about dealing with stunting. The aim of carrying out this service is to increase the knowledge of mother’s and the Pattiro Sompe Village community regarding stunting. The method used is lecture and question and answer. And using pre and post test counseling questionnairesto determine the increase in mother’s knowledge before and after the counseling was carried out. The result of community service activities in stunting education is that there is a significant increase in mother’s knowledge about stunting.